Análisis de la comercialización de calzado equilibrio a través de las redes sociales de la Empresa Disprotextil S.A. de la ciudad de Babahoyo - Nagua Bazurto, Mariana Fergie (2020)
The use of social networks is a tool to promote products and even commercial agreements between buyers and sellers, thus reducing advertising costs, this has influenced the growth of the company is the use of social media as a tool to help spread promotions and discounts, as well as attracting people who seek to be part of the company as leading distributors. The management of these technological platforms of the company Disprotextil S.A. It does not reach the expected level of performance despite the fact that the general number of users on networks is high, the official page does not have a greater number of followers, or people who share their publications, their attempt to use the networks being one of the weaknesses of the company, therefore it seeks to determine the causes of the current problem that affects sales